REFORMULATION OF THE LEGAL REGULATION ON THE INTEGRATED HANDLING OF THE POOR BASED ON A WELFARE LEGAL STATE - Anisatul Hamidah; Bayu Dwi Anggono; Dominikus Rato; Iwan Rachmad Soetijono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study analyzes the legal policy of handling the poor in Indonesia, which is constitutionally mandated by Article 34 paragraph (1) of the 1945 Constitution of the Republic of Indonesia as the embodiment of the ideals of a Welfare State. Normatively, this state obligation is implemented through Law Number 13 of 2011 and Law Number 11 of 2009. The results of the study indicate horizontal disharmony and dualism of regulations, data inaccuracy, and weak institutional coordination. This condition creates inefficiency and indicates that poverty handling is still charity-based rather than rights-based. Based on John Rawls' Distributive Justice theory (Difference Principle) and the principles of the Pancasila Welfare State Law, this study proposes an Integrated Codification Strategy for the Law on Handling the Poor. This codification aims to unify legal substances, organize institutional structures, and definitively shift the policy paradigm from compassionate discretion to the obligation to fulfill citizens' human rights in order to realize integrated social justice.